The Relationship Between Learning Outcomes and Fitness Job Placement of Trainers in BLK Dharmasraya District - Wullandari, Tiara; Dwi Arini, Fitri (Universitas Negeri Padang, 2024)
Balai Latihan Kerja (BLK) is one of the institutions that organize non-formal education, which focuses on training skills that are efficient and effective. In organizing training, this institution has policies in its implementation. The role of BLK is as a place to improve the quality of the workforce, and provide training to hone skills to the workforce both dropping out of school and to people who need this training, this training activity is very useful in efforts to increase the potential and expertise of the workforce. The success of the training attended at the vocational training center can be seen from the learning outcomes of the participants. The participants who are interested in learning will pay attention and participate in their participation in the training. This research is quantitative research with a type of correlational method. obtained Based on the learning outcomes of the trainees at the BLK Dharmasraya Regency, categorized as moderate, this can be seen from the percentage value of the correct answers there are as many as 50%, where the value is 50%. The suitability of job placement of trainees at BLK Dharmasraya Regency is categorized as inappropriate